The Metaphorical Use of Language in Deuterocanonical and Cognate Literature - Behnke, Sven,Witte, Markus (De Gruyter, 2015)
Metaphors are a vital linguistic component of religious speech and serve as a cultural indicator of how groups understand themselves and the world. The essays compiled in this volume analyze the use, function, and structure of metaphors in Jewish writings from the Hellenistic-Roman period (including the works of Philo and the texts of Qumran), as well as in apocryphal early Christian texts and inscriptions.
10.1515/9783110373998
Keywords: Konferenzschrift; Metapher; Religiöse Sprache; Frühjudentum; Frühchristentum; Literatur; Christian literature; Early; Jewish religious literature; Metaphor in literature; Metaphor in the Bible; Bibel